3(3x-7)=-75

Simple and best practice solution for 3(3x-7)=-75 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-7)=-75 equation:


Simplifying
3(3x + -7) = -75

Reorder the terms:
3(-7 + 3x) = -75
(-7 * 3 + 3x * 3) = -75
(-21 + 9x) = -75

Solving
-21 + 9x = -75

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 9x = -75 + 21

Combine like terms: -21 + 21 = 0
0 + 9x = -75 + 21
9x = -75 + 21

Combine like terms: -75 + 21 = -54
9x = -54

Divide each side by '9'.
x = -6

Simplifying
x = -6

See similar equations:

| 14x-5=11x+4 | | -28+15-22c=31 | | 5p-2=3p+4 | | -34-7=2 | | a-2.5=7 | | 3-2m=5 | | (3x+7)(12x-6)= | | n-18=-4n | | 4+2(x-3)=-8 | | -3x-8y=-23 | | 4*-2x+5=-2*4x+5 | | 8x=-10+34 | | 2-3n=14-4n | | 4b-1*7=5*7 | | 4*x+2y=16 | | 3{2y-0.3}=19.4-y | | 16=-8-9 | | 8+4+x=9+3 | | 5n-12=103 | | 40=9x-2+20x+5 | | 2=y+6 | | 40=9x-2+20x-5 | | 6{g+3}=-2{g+31} | | 7(2x+3)+5=14x+26 | | 3x+2.4=6 | | 5x=73 | | 42=.5(2x+8)(x+3) | | x+-56=-82 | | y=-x^2+4x+60 | | -6(4x+3)=-6(-4x-3) | | 29x=-58 | | 70+3x=93 |

Equations solver categories